EFEKTIVITAS PENGGUNAAN VOLTASE RENDAH PADA STERILISASI MEDIA BIAKAN BAKTERI - Rodhiansyah Djayasinga (JFL : Jurnal Farmasi Lampung, 2017)
The important treatment of culture media before being used is by sterilizing growth medium first to avoid contamination from contaminant bacteria which can ruin the result of bacteria in treatment ingredients. Nowadays, many researchers develop new methods to sterilize, like; disinfecting microorganisms with electrochemistry, electro-sterilization uses graphite electrode on liquid culture media nutrient broth produces the decrease in bacteria rate by 16.7%.. This research tends experiment whose subject is culture media nutrient broth, dependent variable is a number of dead bacteria and culture media nutrient broth, independent variable is 8 electric potentials, 10 volts, and duration 5 until 10 minutes. Electro-sterilization treatment in subject is 4 with 6 times repeat. Data collecting method use observation instruments of sterility test result culture media nutrient broth. The result of data bivariate analysis uses anova test determined that electro-sterilization will be effective and efficient if it is done in 10 volts for 10 minutes. Data analysis univariate by using frequent distribution determined that it is 8,3% of all total sample contain dead bacteria. Analysis data uses correlation test determined that culture media nutrient broth which has been given electro-sterilization treatment function as culture media. Keywords: Electrosterilization, Electrode, Nutrient Broth